THE DEVELOPMENT AND CHARACTERISATION OF FAST DISSOLVING FILM OF POORLY WATERSOLUBLE DRUG LURASIDONE HYDROCHLORIDE - PRABHU, ANAGHA; Arondeka, ASMITA ARONDEKAR; BHIDE, PRASHANT; SHWETA BORKAR (International Journal of Applied Pharmaceutics, 2021)
Objective: The objective of the present work was to formulate and evaluate a fast-dissolving oral film of lurasidone hydrochlorideused as an atypical antipsychotic for the treatment of schizophrenia capable of providing faster onset of action. Methods: The fastdissolving films of lurasidone hydrochloride were prepared by the solvent casting technique using different compositions and combinations of hydroxypropyl methylcellulose E-3, E-5, E-15, and K4M as fast-dissolving polymer bases. A set of seven formulations were prepared and evaluated for parameters like physical characterization, thickness, weight uniformity, mechanical characteristics (folding endurance,tensile strength), surface pH, in vitro disintegration time, drug content, and an in vitro drug release. Results: The prepared films exhibited uniform and a smooth surface with uniform weight, thicknessand 89-90% mg drug content. The formulation F7 Showed excellent elasticity and disintegration within seconds. Lurasidone hydrochloride was rapidly released in vitro from all formulations. The release was found to be rapid and maximum of 41.5% in Phosphate buffer pH 6.8 and 58.6% in 0.1 N hydrochloric acid over a period of 30 min. The further optimized formulation F7Adepicted a faster and maximum release of 78% as compared to the marketed tablet 74%. Conclusion: The developed formulation is a better alternative to tablets by its ability to produce good drug release.